Hypervirulent Klebsiella pneumoniae Endogenous Endophthalmitis—A Global Emerging Disease - Serban, Dragos; Popa Cherecheanu, Alina; Dascalu, Ana Maria; Socea, Bogdan; Vancea, Geta; Stana, Daniela; Smarandache, Gabriel Catalin; Sabau, Alexandru Dan; Costea, Daniel Ovidiu (Life (Basel, Switzerland), 2021)
The review aims to document the new emerging hypervirulent Klebsiella pneumoniae (Kp) endogenous endophthalmitis (EKE) in terms of incidence, microbiological characterization of the pathogenic agent, associated risk factors, management, and outcomes. Hypervirulent (hv) strains of KP (hvKp) induce invasive liver abscesses (LA) with specific clinical features. Up to 80–90% of cases have hepatic liver abscess as a primary focus of infection, followed by renal or lung hvKp infections. However, the incidence of EKE in patients with KPLA varied between 3.4% (19) and 12.6% (13), with a total of 95 cases of endophthalmitis in 1455 cases of KPLA (6.5%). Severe visual loss was encountered in 75% of cases, with 25% bilateral involvement. Intravitreal antibiotics are the mainstay therapeutic approach. Pars plana vitrectomy is a subject of controversy. HvKp strains present mostly natural “wild-type” antibiotic resistance profile suggestive for community-acquired infections, being highly susceptive to the third and fourth generation of cephalosporins and carbapenems. Antimicrobial resistance in hypervirulent strains was recently documented via plasmid transfer and may result in extremely difficult to treat cases. Global dissemination of these strains is a major epidemiologic shift that should be considered in the diagnostic and therapeutic management of patients with endogenous endophthalmitis. Ophthalmologic screening in patients with KPLA and other hvKp infections and a multidisciplinary therapeutic approach is extremely important for early diagnosis and preservation of the visual function.